Parent Management Training Combined with Group-CBT Compared to Parent Management Training Only for Oppositional Defiant Disorder Symptoms: 2-Year Follow-Up of a Randomized Controlled Trial - Helander, Maria; Enebrink, Pia; Hellner, Clara; Ahlen, Johan (Child psychiatry and human development, 2023)
Parent management training (PMT) is recommended treatment for children with oppositional defiant disorder (ODD) and child-directed cognitive behavior therapy (CBT) is also recommended for school-aged children. The current study examined 2-year follow-up effects of parent management training (PMT) combined with the CBT based group intervention Coping Power Program (CPP) compared to PMT only. Results showed long-term effectiveness of both PMT and PMT combined with CPP in reduced disruptive behavior problems and harsh parenting strategies, and increased emotion regulation- and social communication skills. The earlier reported increase in emotion regulation- and social communication skills in the PMT with CPP condition during treatment remained stable while the PMT condition showed continued improvement during the follow-up period. To conclude, PMT with CPP did generally not provide significant benefits at the 2-year follow-up compared to PMT, apart from an improvement earlier in time regarding emotion regulation- and social communication skills. Trial registration number ISRCTN10834473, date of registration: 23/12/2015.